Anionic electrodeposition coating composition and coated article
The anionic electrodeposition coating composition, featuring a polyimide resin with a bisphenol backbone and a basic compound, addresses the issues of low storage stability and insufficient thermal performance in existing coatings, achieving enhanced stability and thermal resistance.
Patent Information
- Application Number
- JP2023181040
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
Existing anionic electrodeposition coating compositions face challenges with low storage stability, difficulty in forming thick, uniform coatings, and insufficient thermal shock resistance, heat resistance, and substrate adhesion.
An anionic electrodeposition coating composition containing a polyimide resin (A) with a bisphenol backbone and a basic compound (B), which enhances electrical conductivity and improves film formation properties, thermal shock resistance, and substrate adhesion.
The composition achieves high storage stability and forms coatings with excellent thermal shock resistance, heat resistance, and substrate adhesion, even in thick films, thereby addressing the limitations of prior art.
Smart Images

Figure 2025070593000001 
Figure 2025070593000002 
Figure 2025070593000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an anionic electrodeposition coating composition that can be suitably used for forming a coating film in anionic electrodeposition coating, and to a coated article. [Background technology]
[0002] Electrodeposition coating is a coating method in which a metal or other substrate and a pair of electrodes for the substrate are immersed in an electrodeposition paint, a voltage is applied, and the charged coating film-forming components in the paint are electrophoresed and precipitated on the substrate to form a coating film. Electrodeposition coating can form a coating film of uniform thickness even if the substrate has a complex shape, and is also excellent in edge coverage. Compared with spray coating and dipping coating, it can form a coating film without unevenness, so it is used in various fields such as automobile parts, building materials, and electronic material parts for the purpose of improving the corrosion resistance, water resistance, durability, etc. of the substrate. In addition, since electrodeposition coating can be applied with a small amount of organic solvent, it is an extremely excellent coating method from the viewpoint of volatile organic compounds (VOC) countermeasures. Depending on the charge of the coating film-forming components, electrodeposition coating can be divided into anionic electrodeposition coating and cationic electrodeposition coating. Of these, anionic electrodeposition coating is a coating method in which an anionic electrocoating paint carrying an anionic charge is electrodeposited onto the substrate, which acts as the anode, and is widely used in the field of building materials, etc.
[0003] In recent years, in the fields of electronics and mobility, materials with high heat resistance, durability, insulation, etc. are required in line with the trend toward high functionality, miniaturization, and weight reduction. In particular, in electric vehicles such as electric vehicles (EVs) and hybrid vehicles (HVs), paints that can uniformly form insulating coatings with long-term heat resistance, etc., are required for components that are becoming smaller and more complex in order to achieve, for example, smaller motors and higher output. In addition, in order to maintain performance and safety over a long period of time even in environments with extreme temperature differences, from use in cold regions to high-temperature environments during driving, there is a strong demand for paints that can form highly durable insulating coatings with excellent thermal shock resistance, can obtain uniform coatings even in thick films, and have excellent storage stability.
[0004] In response to such demands, electrodeposition paints using polyimide resins, polyamideimide resins, and the like, which exhibit excellent electrical insulation properties, heat resistance, mechanical properties, solvent resistance, chemical resistance, and the like, have been investigated.
[0005] Patent Document 1 discloses an electrodeposition coating composition comprising a neutralized salt of a polyamic acid, which is a reaction product of an aromatic tetracarboxylic dianhydride and an aromatic diamine, a polar solvent for dissolving the polyamic acid, water, and an alcohol having a phenyl group, a furfuryl group, or a naphthyl group. However, since the polyamic acid of the polyimide precursor is easily hydrolyzed with water, the storage stability of the coating composition is low. In addition, since the polyamic acid contained in the electrodeposition coating film is imidized by dehydrating and cyclizing it by heating at high temperature and for a long time, there are problems in that the heat resistance and thermal shock resistance of the resulting coating film are insufficient due to the coating film distortion and film reduction caused by volume reduction, and polyamic acid is not completely imidized and remains.
[0006] Patent Document 2 discloses a suspension-type polyimide electrodeposition paint that has siloxane bonds in the molecular skeleton and dispersed particles of block copolymerized polyimide having anionic groups in the molecule, and can form an electrodeposition coating with extremely uniform film properties at a high electrodeposition rate. However, since the electrical conductivity of the electrodeposition paint is low, it is difficult to continue the electrophoresis of the coating film-forming components (growth of the coating film) caused by current flow during electrodeposition coating, and it is difficult to obtain a thick and uniform coating film. In addition, since an aliphatic polysiloxane structure and an anionic group are introduced into the polyimide main chain by block copolymerization, there is a problem that the heat resistance and thermal shock resistance of the coating are insufficient.
[0007] Patent Document 3 discloses a resin composition comprising polyimide particles, either an organic solvent solution of polyimide or an organic solvent solution of a polyimide prepolymer, and a hydrophilic cationic polymer, as well as a water-based electrodeposition paint using the resin composition. However, since the hydrophilic cationic polymer used is inferior in heat resistance and durability to polyimide, there is a problem that the heat resistance and thermal shock resistance of the coating film are insufficient.
[0008] Patent Document 4 discloses a resin for forming an insulating film, which is characterized by a bond between an NCO group of a polyimide having an isocyanate (NCO) group at the end and a hydroxyl group of a linear diol or a thiol of a linear dithiol, and an electrodeposition liquid containing the resin for forming an insulating film, a polar solvent, water, a poor solvent, and a base. However, the resulting coating film does not satisfy the long-term heat resistance required for automobile parts and the like, and there is a problem in that the thermal shock resistance of the coating film is insufficient.
[0009] Patent Document 5 discloses an electrodeposition coating composition containing a polyamic acid derivative having a specific repeating structural unit, a hydrophobic amine compound, a hydrophilic amine compound, and an aprotic solvent. However, since the electrodeposition coating film is imidized by dealcoholization and ring closure in the drying process, it is difficult to form a smooth and uniform coating film, especially a thick film, and furthermore, since it has a rigid structure with high heat resistance, there are problems in that the insulating properties and thermal shock resistance of the obtained coating film are insufficient. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 9-124978 [Patent Document 2] JP 2011-256318 A [Patent Document 3] JP 2006-052268 A [Patent Document 4] JP 2019-094404 A [Patent Document 5] JP 2023-80873 A Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made to solve the problems of the conventional technology described above, and aims to provide an anionic electrodeposition coating composition having excellent storage stability which, when used in electrodeposition coating, can provide a coating film with excellent appearance even in a thick film and which is excellent in thermal shock resistance, insulating properties, heat resistance and adhesion to a substrate, and a coated article using the same. [Means for solving the problem]
[0012] The anionic electrodeposition coating composition of the present invention (hereinafter sometimes simply referred to as electrodeposition coating) contains a polyimide resin (A) which is a polycondensate of an acid dianhydride and a diamine, and a basic compound (B), in which at least one of the acid dianhydride and the diamine constituting the polyimide resin (A) has a bisphenol skeleton, and has an electrical conductivity of 300 to 2500 μS / cm. Effect of the Invention
[0013] According to the present invention described above, it is possible to provide an anionic electrodeposition coating composition which has high storage stability and which provides a coating film formed by anionic electrodeposition coating with excellent coating film appearance, thermal shock resistance, insulating properties, heat resistance and substrate adhesion, and a coated article using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The anionic electrodeposition coating composition and the coated article of the present invention will now be described. In the present invention, an imide bond is defined as consisting of one nitrogen atom and two carbonyl bonds (C=O), and an acid anhydride group refers to a group represented by -C(=O)-OC(=O)-. In the present invention, (iso)alkyl includes both normal alkyl (n-alkyl) and isoalkyl (alkyl can include specific alkyl groups such as propyl and butyl). In this specification, the coating film refers to a film formed by electrodeposition coating of an anionic electrodeposition coating composition on a substrate such as a metal plate, followed by baking. In addition, in this specification, a numerical range specified using "to" is intended to include the numerical values before and after "to" as the lower and upper limit values of the range.
[0015] <Anionic electrodeposition coating composition> The anionic electrodeposition coating composition of the present invention contains a polyimide resin (A) and a basic compound (B).
[0016] <Polyimide resin (A)> The polyimide resin (A) used in the present invention is a polycondensation product of an acid dianhydride and a diamine, and at least one of the acid dianhydride and the diamine has a bisphenol skeleton, that is, the polyimide resin (A) has a bisphenol skeleton.
[0017] The polyimide resin (A) has a bisphenol skeleton, which provides excellent heat resistance, excellent electrical insulation, and a flexible structure, which provides excellent mechanical strength and adhesion to substrates. In addition, because the bisphenol skeleton is a large molecular weight structure, the number of imide bonds in the molecule can be suppressed even if the molecular weight of the polyimide resin (A) is increased, resulting in a polyimide resin with excellent solvent solubility and easy aqueous conversion. By using the polyimide resin (A) in an anionic electrodeposition coating composition, the resulting anionic electrodeposition coating composition has excellent storage stability, and a coating film having excellent heat resistance, insulating properties, and thermal shock resistance can be obtained.
[0018] The bisphenol skeleton in the present invention is a structure represented by the following general formula (1). (Formula 1) JPEG2025070593000001.jpg45120X in formula (1) is a divalent linking group, and examples thereof include -C(CH3)2-, -C(CF3)2-, -SO2-, -CH(CH3)-, -CH2-, -C(CH3)(Ph)-, -C(CH3)(CH2CH3)-, -C(CH3)2-Ph-C(CH3)2-, etc. Ph represents a phenyl group. The bisphenol skeleton having the linking group is called a bisphenol A skeleton, a bisphenol AF skeleton, a bisphenol S skeleton, a bisphenol E skeleton, a bisphenol F skeleton, a bisphenol AP skeleton, a bisphenol B skeleton, a bisphenol M skeleton, or a bisphenol P skeleton, in that order. Among these, X in formula (1) is preferably -C(CH3)2- from the viewpoints of the solvent solubility of the polyimide resin, and also the heat resistance, thermal shock resistance, and substrate adhesion of the resulting coating film, etc. In other words, the polyimide resin (A) preferably has a bisphenol A skeleton. In addition, R in formula (1) is each independently a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, an amino group, or a halogen atom, and the hydrocarbon group may be substituted with a halogen. When there are multiple R, the multiple R may be the same or different.
[0019] Of the total 100 mol% of the acid dianhydrides and diamines constituting the polyimide resin (A), the total content of the acid dianhydrides and diamines having a bisphenol skeleton is preferably 40 mol% or more, more preferably 50 mol% or more, and particularly preferably 55 mol% or more. If the content is more than the above, the storage stability of the anionic electrodeposition coating composition is superior, and the film-forming property during electrodeposition coating is superior, so that a good coating appearance can be obtained even in a thick film. In addition, the thermal shock resistance and substrate adhesion of the resulting coating film are superior. The total content of the acid dianhydride having a bisphenol skeleton and the diamine may be 100 mol %.
[0020] Specific examples of acid dianhydrides having a bisphenol skeleton include 4,4'-(4,4'-isopropylidenediphenoxy)bisphthalic dianhydride, 4,4'-(4,4'-methylenediphenoxy)bisphthalic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, etc. These can be used alone or in combination of two or more.
[0021] Specific examples of diamines having a bisphenol skeleton include aromatic diamines such as 4,4'-isopropylidenebis[(4-aminophenoxy)benzene], 4,4'-(hexafluoroisopropylidene)bis[(4-aminophenoxy)benzene], bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)phenylsulfone, and 6,6'-[(1-methylethylidene)-bis(-4,1-phenyleneoxy)]-bis-3-pyridine-amine; Examples of the aromatic diamines include aromatic diamines having a hydroxyl group, such as bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, and bis(3-amino-4-hydroxyphenyl)fluorene. These may be used alone or in combination of two or more.
[0022] As the polyimide resin (A), an acid dianhydride other than an acid dianhydride having a bisphenol skeleton and a diamine other than a diamine having a bisphenol skeleton can be used as long as at least one of the acid dianhydride and the diamine has a bisphenol skeleton.
[0023] The acid dianhydride other than the acid dianhydride having a bisphenol skeleton is not particularly limited, and examples thereof include pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 3,3',4,4'-diphenyltetracarboxylic dianhydride, and the like. aromatic tetracarboxylic dianhydrides such as arylsulfone tetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 1,1,1,3,3,3-hexafluoro-2,2-bis(2,3- or 3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimellitic acid monoester acid anhydride), and ethylene glycol bisanhydrotrimellitate; Cyclobutane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1-carboxymethyl-2,3,5-cyclopentanetricarboxylic acid, 3-carboxymethyl-1,2,4-cyclopentanetricarboxylic acid, rel-dicyclohexyl-3,3',4,4'-tetracarboxylic acid, tricyclo[4.2.2.02,5]de Carboxymethylbicyclo[2.2.1]heptane-2,3,6-tricarboxylic acid, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2.2.2]octane-7-ene-2,3,6,7-tetracarboxylic acid, bicyclo[3.3.0]octane-2,4,6,7-tetracarboxylic acid, 7,8-diphenylbicyclo[2.2.2]octane-7-ene-2,3,5,6-tetracarboxylic acid, Cyclo-, bicyclo-, and tricyclotetracarboxylic acids such as 4,8-diphenyl-1,5-diazabicyclooctane-2,3,6,7-tetracarboxylic acid, 9-oxatricyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic acid, and 9,14-dioxopentacyclo[8.2.11,11.14,7.02,10.03,8]tetradecane-5,6,12,13-tetracarboxylic acid; and stilbene such as 2,8-dioxaspiro[4.5]decane-1,3,7,9-tetradecane. Pyrocyclic tetracarboxylic acids; alicyclic tetracarboxylic dianhydrides such as 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride; Examples of the dianhydride include aliphatic tetracarboxylic acid dianhydrides such as 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 1,2,4,5-pentanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, and 1,2,5,6-hexanetetracarboxylic acid. From the viewpoint of the heat resistance and thermal shock resistance of the resulting coating film, it is preferable to use aromatic tetracarboxylic acid dianhydrides. These may also be used in combination of two or more.
[0024] Diamines other than the diamine having a bisphenol skeleton are not particularly limited, and aromatic diamines having a hydroxyl group such as bis(3-amino-4-hydroxy)biphenyl, 2,2'-ditrifluoromethyl-5,5'-dihydroxyl-4,4'-diaminobiphenyl, and 2,2'-bis(trifluoromethyl)-5,5'-dihydroxybenzidine; 1,4-Diaminobenzene, 1,3-Diaminobenzene, 1,2-Diaminobenzene, 1,5-Diaminonaphthalene, 1,8-Diaminonaphthalene, 2,3-Diaminonaphthalene, 2,6-Diaminotoluene, 2,4-Diaminotoluene, 3,4-Diaminotoluene, 4,4'-Diaminodiphenylmethane, 3,4'-Diaminodiphenylether, 4,4'-Diaminodiphenylether, 4,4'-Diamino-1,2-diphenylethane, 3,3'-Diaminodiphenyl aromatic diamines such as phenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylsulfone, 3,3'-diaminobenzophenone, 3,3'-diaminodiphenylsulfone, 3,5-diaminobenzoic acid, 2,4-diaminophenylacetic acid, 2,5-diaminoterephthalic acid, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 2,5-diaminobenzenesulfonic acid, and o-tolidinedisulfonic acid; Alicyclic diamines such as isophoronediamine, norbornanediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, and piperazine; Aliphatic diamines such as ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,9-nonanediamine, 1,12-dodecamethylenediamine, metaxylenediamine, and dimer diamine; Examples of the diamine include diamines having a siloxane skeleton. From the viewpoint of the heat resistance and thermal shock resistance of the resulting coating film, it is preferable to use an aromatic diamine. These may be used in combination of two or more kinds.
[0025] For the purpose of improving the storage stability of the anionic electrodeposition coating composition, the thermal shock resistance of the coating film, the adhesion to substrates, etc., the polyimide resin (A) preferably has hydroxyl groups in the molecule, and more preferably has phenolic hydroxyl groups.
[0026] The method for introducing hydroxyl groups into the polyimide resin (A) is not particularly limited, but from the standpoint of the storage stability of the anionic electrodeposition coating composition and the heat resistance and thermal shock resistance of the resulting coating film, a method for introducing the groups by reaction of an acid dianhydride with a diamine having a hydroxyl group is preferred.
[0027] In 100 mol % of the diamine component, the content of the diamine having a hydroxyl group is preferably 5 to 55 mol %, more preferably 7 to 50 mol %, and particularly preferably 10 to 45 mol %. If it is equal to or more than the lower limit, the storage stability of the anionic electrodeposition coating composition is superior, and the substrate adhesion of the resulting coating film is superior. If it is equal to or less than the upper limit, the heat resistance and thermal shock resistance of the coating film are superior.
[0028] Examples of the diamine having a hydroxyl group include the diamine having a bisphenol skeleton and the aromatic diamine having a hydroxyl group exemplified as the diamine other than the diamine having a bisphenol skeleton. In addition, a substituent may be introduced into any position of these compounds.
[0029] The diamine may contain a diamine having a siloxane skeleton for the purpose of improving the insulating property and thermal shock resistance of the coating film. The diamine having a siloxane skeleton is not particularly limited as long as it can be imidized with an acid dianhydride, and commercially available products can be suitably used, such as KF-8010, X-22-161A, X-22-161B, KF-8012, X-22-9409, and X-22-1660B-3 manufactured by Shin-Etsu Chemical Co., Ltd., BY-16-853U and BY-16-853 manufactured by Dow Toray, and Silaplane FM-3311 manufactured by JNC Corporation, which may be used alone or in combination of two or more kinds.
[0030] The polyimide resin (A) preferably has an acid anhydride group at the molecular chain end. By having an acid anhydride group at the molecular chain end, the acid anhydride group is opened to generate two equivalent carboxyl groups, which can be easily neutralized with a basic compound (B) to make the polyimide resin water-based, and the storage stability of the anionic electrodeposition coating composition is improved. The method for obtaining the acid anhydride-terminated polyimide resin (A) is not particularly limited, and the resin can be produced by a known method. The molecular chain end refers to a repeating structural unit at the end of the molecular chain of the polyimide resin (A), or a non-repeating structure linked to the end.
[0031] The structure of the molecular chain terminal of the polyimide resin (A) may be partially changed. The terminal structure is not particularly limited, but examples thereof include a carboxyl group, an amino group, a hydroxyl group, an alkyl group, an alkylene group, and an aryl group. The method for converting the structure of the molecular chain terminal is not particularly limited, but an example is a method in which an acid anhydride-terminated polyimide resin is synthesized and then further reacted with an amine compound.
[0032] The polyimide resin (A) can be produced by various known methods. Specific examples include a method of converting a polyimide precursor, a polyamic acid resin or a polyamic acid ester resin, into an imide group by heating to cyclize it. For example, a method of synthesizing a polyamic acid resin includes a method of reacting an acid dianhydride with a diamine. More specifically, a monomer containing an acid dianhydride and a diamine is dissolved in a solvent and stirred at a temperature of, for example, 60 to 120°C for 0.1 to 2 hours to polymerize it, thereby producing a polyamic acid resin, which is a polyimide precursor. As the equivalent ratio (molar ratio) of the acid dianhydride to the diamine, for example, the equivalent ratio of the acid dianhydride to the diamine can be 0.5 to 1.0, preferably 0.6 to 0.95. There is also a method of reacting an acid dianhydride with a diisocyanate to obtain a polyimide precursor, and then obtaining a polyimide resin.
[0033] Examples of the synthesis method of the polyamic acid ester resin include a method in which a diester is obtained from a tetracarboxylic dianhydride and an alcohol, and then the diester is reacted with a diamine in the presence of a condensing agent, and a method in which a diester is obtained from a tetracarboxylic dianhydride and an alcohol, and then the remaining dicarboxylic acid is converted into an acid chloride and reacted with a diamine.
[0034] Examples of organic solvents used in polymerization include N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. The solvents are used alone or in combination of two or more. Aromatic hydrocarbons such as xylene and toluene can also be used in combination.
[0035] The method of imidizing the polyimide precursor to obtain a polyimide resin is not particularly limited, but may be, for example, a method of heating in a solvent at a temperature of 80 to 400°C for 0.5 to 50 hours. At this time, a catalyst and / or a dehydrating agent may be used as necessary. Examples of reaction catalysts include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, and heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline. Examples of dehydrating agents include aliphatic acid anhydrides such as acetic anhydride and aromatic acid anhydrides such as benzoic anhydride.
[0036] The imidization rate (imide ring formation rate) is not limited, but from the viewpoint of the heat resistance and thermal shock resistance of the resulting coating film, it is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. The imidization rate in this specification can be easily determined by the following method. First, the infrared absorption spectrum of the polyimide resin is measured, and the absorption peak of the imide ring structure (1780 cm -1 Near, 1380cm -1 Next, the polyimide resin is heat-treated at 350°C for 1 hour and the infrared absorption spectrum is measured. This is used as a sample with an imidization rate of 100%, and the 1380 cm -1 By comparing the intensity of the peaks near the peaks, the imide group content in the polyimide resin before heat treatment can be calculated, and the imidization rate can be obtained.
[0037] The acid value of the polyimide resin (A) is preferably from 6 to 80 mgKOH / g, more preferably from 8 to 60 mgKOH / g, and particularly preferably from 10 to 50 mgKOH / g. When the acid value is equal to or greater than the lower limit, the coating film has better substrate adhesion and the anionic electrodeposition coating composition has better storage stability, whereas when the acid value is equal to or less than the upper limit, the coating film has better thermal shock resistance and heat resistance. The method for measuring the acid value will be described in detail in the Examples.
[0038] The weight average molecular weight of the polyimide resin (A) is preferably from 5,000 to 50,000, more preferably from 8,000 to 40,000, and particularly preferably from 10,000 to 35,000. When the weight average molecular weight is equal to or greater than the lower limit, the coating film has better thermal shock resistance and heat resistance, whereas when the weight average molecular weight is equal to or less than the upper limit, the coating film has better substrate adhesion and the anionic electrodeposition coating composition has better storage stability. The weight average molecular weight is a value calculated as polystyrene by measuring by gel permeation chromatography (GPC).
[0039] <Basic Compound (B)> The basic compound (B) used in the present invention is used for the purpose of neutralizing the carboxyl groups present in the polyimide resin (A) and the carboxyl groups formed by ring-opening of the acid anhydride groups, thereby imparting hydrophilicity. Examples of the basic compound (B) include organic amine compounds, ammonia, and hydroxides of alkali metals.
[0040] Examples of the organic amine compound include alkylamine compounds such as monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, triethylamine, monopropylamine, dipropylamine, tripropylamine, monobutylamine, dibutylamine, tributylamine, benzylamine, N-methylbenzylamine, and dimethylbenzylamine; Alkanolamine compounds such as monoethanolamine, diethanolamine, triethanolamine, N,N-dimethyl-ethanolamine (also known as dimethylaminoethanol), N,N-diethyl-ethanolamine, 2-dimethylamino-2-methyl-1-propanol, 2-amino-2-methyl-1-propanol, N-methyldiethanolamine, N-ethyldiethanolamine, monoisopropanolamine, diisopropanolamine, and triisopropanolamine; Examples of the heterocyclic amine compounds include pyrrole, imidazole, oxazole, pyrazole, thiazole, pyridine, pyridazine, pyrimidine, pyrazine, piperidine, piperazine, morpholine, and N-methylmorpholine. Examples of the alkali metal hydroxide include lithium hydroxide, sodium hydroxide, and potassium hydroxide. The basic compound (B) may be used alone or in combination of two or more kinds, and these may be added at once or in several portions.
[0041] The basic compound (B) preferably contains an organic amine compound, and among the organic amine compounds, it is particularly preferable to contain at least one of an alkanolamine compound and a heterocyclic amine compound. By containing at least one of the alkanolamine compound and the heterocyclic amine compound, the storage stability of the obtained electrodeposition paint is more excellent, the film-forming property during electrodeposition coating is improved, and a more excellent coating appearance is obtained.
[0042] The amount of the basic compound (B) to be added is preferably 0.6 to 3.0 equivalents relative to the acid value in the polyimide resin (A), more preferably 0.8 to 2.7 equivalents, and particularly preferably 1.0 to 2.5 equivalents. When the amount of the basic compound (B) is within the above range, the storage stability of the electrodeposition paint is superior, the film-forming properties during electrodeposition coating are improved, and a superior coating appearance is obtained, resulting in superior thermal shock resistance, insulating properties, substrate adhesion, etc. of the coating film.
[0043] <Organic solvent (C)> An anionic electrodeposition coating composition generally contains water and an organic solvent as a solvent. In the present invention, it is also preferable to contain an organic solvent (C), and by containing the organic solvent (C), for example, it is possible to improve the film-forming property during electrodeposition coating, and to improve the coating appearance, the substrate adhesion of the coating film, the thermal shock resistance, the insulating property, etc. The organic solvent (C) can be used alone or in combination of two or more kinds.
[0044] The organic solvent (C) is contained in an amount of preferably 3.0 to 25.0 mass %, more preferably 4.0 to 20.0 mass %, and particularly preferably 5.0 to 18.0 mass %, based on 100 mass % of the electrodeposition coating material. When the content of the organic solvent (C) is 3.0 to 25.0% by mass, the film-forming properties during electrodeposition coating are improved, and a better coating appearance is obtained, leading to better thermal shock resistance, insulating properties, substrate adhesion, etc. of the coating. The water content is preferably 50 to 97% by mass, more preferably 55 to 96% by mass, and particularly preferably 60 to 95% by mass, based on 100% by mass of the electrodeposition coating composition.
[0045] In addition, the organic solvent (C) preferably contains an organic solvent (C-1) having an ether group in the molecule. By containing the organic solvent (C-1) having an ether group in the molecule, the storage stability of the electrodeposition paint is more excellent, the film-forming properties during electrodeposition coating and baking are improved, and a more excellent coating appearance is obtained, so that the coating film has more excellent thermal shock resistance, insulation properties, substrate adhesion, etc. The organic solvent (C) may be composed of the organic solvent (C-1) alone, or may be mixed with an organic solvent different from the organic solvent (C-1) as required.
[0046] Examples of the organic solvent having an ether group in the molecule include ethers such as dimethyl ether, diethyl ether, and diisopropyl ether; Alkylene glycol monoalkyl ethers having an alkyl group of 1 to 8 carbon atoms, such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono(iso)propyl ether, ethylene glycol mono(iso)butyl ether, ethylene glycol mono-tert-butyl ether, ethylene glycol monohexyl ether, 3-methoxybutanol, 3-methyl-3-methoxybutanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono(iso)propyl ether, diethylene glycol mono(iso)butyl ether, diethylene glycol monohexyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono(iso)propyl ether, propylene glycol mono(iso)butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono(iso)propyl ether, and dipropylene glycol mono(iso)butyl ether; Alkylene glycol dialkyl ethers in which the alkyl group has 1 to 8 carbon atoms, such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di(iso)propyl ether, ethylene glycol di(iso)butyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol di(iso)propyl ether, diethylene glycol di(iso)butyl ether, diethylene glycol dihexyl ether, triethylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol di(iso)propyl ether, propylene glycol di(iso)butyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol di(iso)propyl ether, and dipropylene glycol di(iso)butyl ether; Acetates such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, ethylene glycol monobutyl ether acetate, and 3-methyl-3-methoxybutyl acetate; Organic solvents such as cyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 4-methyltetrahydropyran, and 1,4-dioxane can be used appropriately.
[0047] Among these, from the viewpoints of storage stability of the electrodeposition paint, film-forming properties during electrodeposition coating, and solvent evaporation rate during baking, it is more preferable to include at least one of an alkylene glycol monoalkyl ether in which the alkyl group has 1 to 8 carbon atoms and an alkylene glycol dialkyl ether in which the alkyl group has 1 to 8 carbon atoms.
[0048] The organic solvent (C-1) having an ether group in the molecule preferably accounts for 50 mass % or more, more preferably 60 mass % or more, and particularly preferably 70 mass % or more, of 100 mass % of the organic solvent (C). When the content of the organic solvent (C-1) in 100 mass% of the organic solvent (C) is 50 mass% or more, the storage stability of the electrodeposition paint is superior, the film-forming properties during electrodeposition coating and baking are improved, and a superior coating appearance is obtained, resulting in superior thermal shock resistance, insulating properties, substrate adhesion, etc. of the coating film.
[0049] The organic solvent (C) may contain an organic solvent other than the organic solvent (C-1) having an ether group in the molecule. The organic solvent is not particularly limited, but it is preferable to use an organic solvent that can dissolve or disperse each component such as the polyimide resin (A). Specific examples of such solvents include hexane, heptane, octane, decane, amylbenzene, isopropylbenzene, ethylbenzene, o-xylene, m-xylene, p-xylene, 1,2-diethylbenzene, 1,3-diethylbenzene, 1,4-diethylbenzene, cyclohexylbenzene, 2,6-dimethylnaphthalene, p-cymene, styrene, tetralin, α-pinene, β-pinene, dodecylbenzene, toluene, and mesitylene, as well as hydrocarbon solvents such as Swazol 1000, Swazol 1500 (all manufactured by Maruzen Petrochemical Co., Ltd.), T-SOL100FLUID, and T-SOL150FLUID (all manufactured by JXTG Nippon Oil & Energy Corporation); Ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, and isophorone; Ester solvents such as ethyl acetate, butyl acetate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, and FlexiSolv DBE esters (manufactured by INVISTA); Examples of alcohol-based solvents include methanol, ethanol, n-amyl alcohol, s-amyl alcohol, t-amyl alcohol, isoamyl alcohol, isobutyl alcohol, isopropyl alcohol, 2-ethylbutanol, 2-ethylhexanol, 2-octanol, n-octanol, neopentyl alcohol, n-butanol, s-butanol, t-butanol, 1-propanol, n-hexanol, 2-heptanol, 3-heptanol, n-heptanol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-2-butanol, and 4-methyl-2-pentanol.
[0050] <Hardening agent (D)> The anionic electrodeposition coating composition of the present invention preferably further contains a curing agent (D) for the purpose of improving the heat resistance, thermal shock resistance, substrate adhesion, etc. of the coating film. As the curing agent (D), a blocked polyisocyanate compound, an epoxy group-containing compound, a phenol resin, an amino resin, a carbodiimide group-containing compound, a maleimide group-containing compound, a metal chelate compound, a β-hydroxyalkylamide compound, etc. can be used. Among them, a blocked polyisocyanate compound or an epoxy group-containing compound is more preferable, and a blocked polyisocyanate compound is particularly preferable. The curing agent (D) may be added in one or more types. The curing agent (D) can react with the acid anhydride group and the carboxyl group in the polyimide resin (A). When the polyimide resin (A) has hydroxyl groups, the curing agent (D) can also react with the hydroxyl groups. In addition, the curing agent (D) can also react with the curable functional groups of the curing agent (D).
[0051] Examples of polyisocyanate compounds used in the blocked polyisocyanate compound include aromatic diisocyanate compounds such as 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate; Aliphatic diisocyanate compounds such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; Aromatic and aliphatic diisocyanate compounds such as ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate; Alicyclic diisocyanate compounds such as 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate [also known as isophorone diisocyanate], 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, and 1,4-bis(isocyanatomethyl)cyclohexane; Triisocyanate compounds such as lysine triisocyanate, tris(isocyanatophenyl)methane, and tris(isocyanatophenyl)thiophosphate; Examples of the polyisocyanate compounds include biurets, uretdione, isocyanurates, adducts, polymers of the polyisocyanate compound monomers, and combinations thereof. Examples of blocking agents include dimethylpyrazole, methyl ethyl ketone oxime, cyclohexanone oxime, phenol, active methylene compounds, and ε-caprolactam.
[0052] From the viewpoints of heat resistance, thermal shock resistance, and adhesion to substrates, the blocked polyisocyanate compound preferably has three or more isocyanate groups.
[0053] The blocked polyisocyanate compound may be a commercially available product. Examples of commercially available products that can be preferably used include Duranate 17B-60P, TPA-B80E, MF-B60B, SBB-70P, and SBN-70D manufactured by Asahi Kasei Corporation, Desmodur BL3272MPA, BL3475BA / SN, BL3575 / 1 MPA / SN, and BL4265SN manufactured by COVENSTRO AG, VESTANAT B1358A, B1370, and B1186A manufactured by EVONIK, and Coronate BI-301, 2507, and 2554 manufactured by Tosoh Corporation.
[0054] The epoxy group-containing compound is not particularly limited as long as it is a compound having two or more epoxy groups in the molecule. Examples of the epoxy group-containing compound include glycidyl ether type epoxy resins such as hydroquinone diglycidyl ether, resorcinol diglycidyl ether, catechol diglycidyl ether, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, biphenol type epoxy resin, and tetramethylbiphenol type epoxy resin; glycidyl ester type epoxy resins such as diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate; Cycloaliphatic (alicyclic) epoxy resins such as epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl)adipate; Multifunctional epoxy resins such as tris(glycidyloxyphenyl)methane, tetrakis(glycidyloxyphenyl)ethane, tetraglycidyldiaminodiphenylmethane, triglycidyl para-aminophenol, triglycidyl meta-aminophenol, tetraglycidyl meta-xylylenediamine, and sorbitol polyglycidyl ether; Examples of the epoxy resin include novolac epoxy resins such as cresol novolac epoxy resins, phenol novolac epoxy resins, α-naphthol novolac epoxy resins, bisphenol A novolac epoxy resins, and brominated phenol novolac epoxy resins.
[0055] An example of the phenol resin is a resin synthesized by an addition condensation reaction between a phenol compound and an aldehyde such as formaldehyde. Examples of the phenol compound include bisphenol A, phenol, o-cresol, p-cresol, m-cresol, p-tert-butylphenol, p-phenylphenol, p-nonylphenol, 2,3-xylenol, 2,5-xylenol, 3,5-xylenol, catechol, resorcinol, and hydroquinone, etc. In this case, the phenol compound may be used alone or in combination of two or more kinds. The phenol resin may also be one in which a part or all of the methylol groups formed by the addition of formaldehyde are etherified with an alcohol.
[0056] Examples of amino resins include resins synthesized by addition condensation reaction of an amino compound such as urea, melamine, or benzoguanamine with an aldehyde such as formaldehyde. In this case, the amino compound may be used alone or in combination of two or more. The amino resin may also be one in which a part or all of the methylol groups formed by the addition of formaldehyde are etherified with an alcohol.
[0057] The carbodiimide group-containing compound is not particularly limited as long as it has two or more carbodiimide groups in the molecule. Examples of the carbodiimide group-containing compound include Carbodilite V-01, V-03, V-05, V-07, and V-09 manufactured by Nisshinbo Chemical Inc., and cyclic carbodiimide manufactured by Teijin Limited.
[0058] The maleimide group-containing compound is not particularly limited as long as it has two or more maleimide groups in the molecule. Examples of the maleimide group-containing compound include o-phenylene bismaleimide, m-phenylene bismaleimide, p-phenylene bismaleimide, 4,4'-diphenylmethane bismaleimide, bisphenol A diphenyl ether bismaleimide, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 4-methyl-1,3-phenylene bismaleimide, and 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide.
[0059] The metal chelate compound is an organometallic compound consisting of a metal and an organic substance, which reacts with the reactive functional group of the polyimide resin (A) or the reactive functional group of the curing agent (D) to form a crosslink. The type of organometallic compound is not particularly limited, and examples thereof include organoaluminum compounds, organotitanium compounds, and organozirconium compounds. The bond between the metal and the organic substance may be a metal-oxygen bond, and is not limited to a metal-carbon bond.
[0060] The β-hydroxyalkylamide compound is not particularly limited as long as it has two or more β-hydroxyalkylamide groups in the molecule, and examples thereof include N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, N,N,N',N'-tetrakis(2-hydroxypropyl)adipamide, etc.
[0061] The curing agent (D) is preferably added in an amount of 1 to 40 parts by mass, more preferably 3 to 35 parts by mass, and particularly preferably 5 to 30 parts by mass, per 100 parts by mass of the polyimide resin (A). By setting the curing agent within this range, the heat resistance, thermal shock resistance, adhesion to substrates, etc. are further improved without impairing the storage stability of the coating material.
[0062] <Other ingredients> A filler can be added to the electrodeposition coating material of the present invention for the purpose of improving the insulating property, heat resistance, thermal shock resistance, etc. of the coating film. The filler is not particularly limited, but examples thereof include crystalline silica, amorphous silica, hollow silica, porous silica, mica, talc, kaolin, clay, hydrotalcite, pyrophyllite, sericite, vermiculite, smectite, bentonite, stevensite, montmorillonite, nontronite, wollastonite, xonotlite, silicon nitride, boron nitride, aluminum nitride, calcium hydrogen phosphate, calcium phosphate, glass flakes, glass beads, wollastonite, hydrated glass, calcium titanate, sepiolite, magnesium sulfate, aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, barium hydroxide, calcium hydroxide, titanium oxide, tin oxide, aluminum oxide, malite, and the like. Examples of the fluorine-containing polymer include magnesium, zirconium oxide, zinc oxide, molybdenum oxide, antimony oxide, nickel oxide, zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, zinc borate, aluminum borate, polytetrafluoroethylene and modified products thereof, tetrafluoroethylene-perfluoroalkyl vinyl ether, tetrafluoroethylene-ethylene, tetrafluoroethylene-hexafluoropropylene, tetrafluoroethylene-vinylidene fluoride, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether, polychlorotrifluoroethylene, chlorotrifluoroethylene-ethylene, chlorotrifluoroethylene-vinylidene fluoride, polyvinylidene fluoride, and polyvinyl fluoride. The shape of the filler is not particularly limited, but examples thereof include spherical, powdery, fibrous, needle-like, and scaly shapes. These fillers may be used alone or in combination of two or more kinds.
[0063] If necessary, a lubricant such as wax can be added to the electrodeposition coating material of the present invention in order to prevent the coating film from being scratched. Suitable waxes include animal and vegetable waxes such as carnauba wax, lanolin wax, palm oil, candelilla wax, and rice wax, petroleum waxes such as paraffin wax, microcrystalline wax, and petrolatum, and synthetic waxes such as polyolefin wax and polytetrafluoroethylene (PTFE) wax.
[0064] The electrodeposition coating material of the present invention may contain a coloring agent such as a pigment or dye, if necessary. Examples of pigments include chromatic pigments (e.g., quinacridone, phthalocyanine, azo, etc.) and achromatic pigments (e.g., titanium oxide, iron oxide, aluminum, carbon black, etc.). These may be used alone or in combination of two or more.
[0065] In addition, for the purpose of improving storage stability, electrodeposition coatability, and the physical properties of the coating film formed, the electrodeposition coating material of the present invention may contain curing catalysts, leveling agents, antifoaming agents, dispersing agents, surfactants, preservatives, antifungal agents, rust inhibitors, pH adjusters, viscosity adjusters, flame retardants, antioxidants, ion collectors, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, electromagnetic wave shielding agents, and the like, depending on the respective purposes and uses.
[0066] <Electrical conductivity> It is important that the electrical conductivity of the electrodeposition paint of the present invention is 300 to 2,500 μS / cm at a paint temperature of 25° C., more preferably 350 to 2,300 μS / cm, and particularly preferably 400 to 2,000 μS / cm. If it is 300 μS / cm or more, the dispersion stability of the polyimide resin (A) in the electrodeposition coating material is excellent, and a sufficient current flows during electrodeposition coating, making it easy to grow a thick coating film and resulting coating film with excellent smoothness. Furthermore, if the resistivity is 2,500 μS / cm or less, excessive current flow during electrodeposition coating is suppressed, and gas generation due to electrolysis of water is suppressed, thereby suppressing the occurrence of coating defects such as gas pinholes, dents, and popping, resulting in a better coating surface appearance. The electrical conductivity can be measured using a commercially available electrical conductivity meter in accordance with JIS K 0130 (general rules for measuring electrical conductivity). The electrical conductivity can be controlled by, for example, the amount of the basic compound (B) or the organic solvent (C) used to neutralize the carboxyl group, and increases by increasing the amount of the basic compound (B) or decreasing the amount of the organic solvent (C). On the other hand, the electrical conductivity decreases by decreasing the amount of the basic compound (B) or increasing the amount of the organic solvent (C).
[0067] The electrodeposition coating of the present invention is produced by neutralizing the carboxyl groups present in the polyimide resin (A) and the carboxyl groups generated by ring-opening the acid anhydride groups with a basic compound (B) in part or in whole, and adding water while stirring. In detail, the polyimide resin (A) is dissolved in an organic solvent (C), and neutralized by adding the basic compound (B) while stirring at a temperature of 10 to 120°C, preferably 20 to 100°C, and then gradually adding water while stirring, and then further adding the organic solvent (C), the curing agent (D), etc. as necessary, and stirring and mixing. The organic solvent (C) and the curing agent (D) can also be added before adding water. The non-volatile content concentration is preferably 1 to 20% by mass, more preferably 1 to 15% by mass.
[0068] In the production of the electrodeposition coating of the present invention, other components used as necessary can be added at any desired timing. The mixing, dispersion or dissolution can be carried out using a mixer, disperser, kneader, or the like, such as a homomixer, homogenizer, disperser, paint shaker, bead mill, sand mill, in-line mixer, or high shear mixer.
[0069] <Painted items> The coated article of the present invention is prepared by electrocoating a substrate with the anionic electrodeposition coating composition by electrocoating.
[0070] Using the electrodeposition paint of the present invention, an uncured coating film can be formed on a substrate by a typical anionic electrodeposition coating technique, and then the coating film can be cured by heating to form a coating film that is a cured product of the electrodeposition paint on the substrate. In the anionic electrodeposition method, for example, the object to be coated is completely or partially immersed in an electrodeposition bath filled with the electrodeposition paint to serve as the anode, and a counter electrode is immersed in the same to apply a voltage between them to perform electrodeposition coating. The object to be coated, to which the electrodeposition paint and its resin component are attached, is then pulled out and the excess electrodeposition paint is washed off in a water bath, and the anionic electrodeposition coated article is then obtained by drying and curing. The coating conditions for anionic electrodeposition coating are not particularly limited and can be appropriately adjusted depending on the type and shape of the substrate, the properties of the electrodeposition paint, the size and shape of the electrodeposition bath, the use and purpose of the substrate, etc. Examples of the coating conditions include a liquid temperature of the electrodeposition paint of 10 to 50°C, an applied voltage of 1 to 400 V, and an electrodeposition time of 10 seconds to 30 minutes. After coating, the uncured coating film is dried and heated to cure. Heating may be performed at 140 to 250°C for about 3 to 60 minutes, and a process of pre-drying at 50 to 130°C for about 3 to 60 minutes and then curing at 140 to 250°C for about 3 to 60 minutes is also preferred. The thickness of the coating film formed is about 1 μm to 150 μm.
[0071] The electrodeposition paint of the present invention is used for the purpose of forming a coating film that covers a substrate. The substrate is not particularly limited as long as it is conductive and can be electrodeposited. For example, copper materials, iron materials, aluminum or aluminum materials treated with anodizing, nickel materials, stainless steel materials, magnesium materials, plated materials or plated articles, metal materials such as die-castings, and surface-treated products thereof, as well as molded products thereof, are preferred. The applications of the electrocoated coated articles include electronic parts, automobile parts, etc., and they are particularly suitable for automobile parts which require excellent insulation properties, heat resistance, thermal shock resistance, etc. EXAMPLES
[0072] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means parts by mass, and "%" means % by mass, unless otherwise specified.
[0073] (Acid value measurement) 1 g of sample (polyimide resin (A)) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 40 mL of N-methyl-2-pyrrolidone and 20 mL of pyridine were added to dissolve. 10 mL of water was added and heated at 80°C for 1 hour to open the acid anhydride groups at the ends. After cooling to room temperature, the solution was titrated using an automatic titrator ("COM-A19" manufactured by Hiranuma Sangyo Co., Ltd.) with 0.1 mol / L alcoholic potassium hydroxide solution as the titrant. The inflection point of the obtained titration curve was used as the end point, and the acid value per non-volatile content of the resin was calculated using the following formula. When multiple inflection points were obtained, the last inflection point was taken as the end point. When the polyimide resin (A) had a phenolic hydroxyl group, the inflection point immediately before the last inflection point was taken as the end point. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Consumption of 0.1 mol / L alcoholic potassium hydroxide solution (mL) F: Potency of 0.1 mol / L alcoholic potassium hydroxide solution
[0074] (Measurement of weight average molecular weight) The weight average molecular weight of the polyimide resin (A) was measured by dissolving the dried resin in tetrahydrofuran to prepare a 0.5% solution, filtering the solution through a membrane filter (13HP045AN, pore size 0.45 μm, manufactured by ADVANTEC Corporation) using the following apparatus and measurement conditions. Equipment: HLC-8420-GPC system (Tosoh Corporation) Column: TSKgel-Super Multipore HZ-M0021488 4.6 mm I.D. x 15 cm x 3 (molecular weight measurement range: 2,000 to approximately 2 million) Elution solvent: tetrahydrofuran Standard material: Polystyrene (Tosoh Corporation) Flow rate: 0.6mL / min Amount of sample solution used: 10μL Column temperature: 40℃
[0075] (Conditions for measuring electrical conductivity) The electrical conductivity of the electrodeposition paint at 25°C was measured using a portable electrical conductivity / pH meter WM-32EP manufactured by DKK-TOA Corporation.
[0076] [Production Example 1] <Synthesis of polyimide resin (A1)> [Production Example 1] In a 1L separable flask equipped with an oil bath and a stirring rod, 700.0 parts of N,N-dimethylformamide were added while introducing nitrogen gas, and 100.4 parts (232 mmol) of Y1-1 (bis[4-(4-aminophenoxy)phenyl]sulfone) as diamine, 51.0 parts (139 mmol) of Y1B-1 (bis(3-amino-4-hydroxyphenyl)hexafluoropropane), and 79.9 parts (93 mmol) of Y2-2 (KF-8010 manufactured by Shin-Etsu Chemical Co., Ltd.) were added while stirring, followed by 268.6 parts (516 mmol) of X1-1 (4,4'-(4,4'-isopropylidenediphenoxy)bisphthalic dianhydride) as an acid dianhydride, and stirred at room temperature for 30 minutes. The mixture was heated to 100 ° C. and stirred for 3 hours, after which the oil bath was removed and the mixture was returned to room temperature to obtain a varnish-like polyimide precursor. Thereafter, while removing the distilled water from the system using a Dean-Stark trap, the mixture was heated at 170°C for 10 hours to obtain a polyimide resin in a varnish state by imidization. The obtained polyimide resin was dried under reduced pressure to remove volatile matters such as the polymerization solvent, thereby obtaining a solid polyimide resin (A1). The acid value and weight average molecular weight (Mw) of the resulting polyimide resin (A1) are shown in Table 1.
[0077] [Manufacturing Examples 2-9, 101] <Synthesis of polyimide resins (A2 to A9, A101)> Polyimide resins (A2) to (A9) and (A101) were obtained in the same manner as in Production Example 1, except that the raw materials and blending amounts were changed to those shown in Table 1. The acid values and weight average molecular weights (Mw) of the obtained polyimide resins are shown in Table 1.
[0078] [Table 1]
[0079] In Table 1, the symbols are as follows: (Acid dianhydride (X)) X1-1: 4,4'-(4,4'-isopropylidenediphenoxy)bisphthalic dianhydride (molecular weight: 520.49) X2-1: 3,3',4,4'-benzophenonetetracarboxylic dianhydride (molecular weight: 322.23) X2-2: 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride (molecular weight: 300.27) (Diamine (Y)) Y1-1: Bis[4-(4-aminophenoxy)phenyl]sulfone (molecular weight: 432.49) Y1-2: 4,4'-isopropylidenebis[(4-aminophenoxy)benzene] (molecular weight: 410.52) Y1B-1: Bis(3-amino-4-hydroxyphenyl)hexafluoropropane (molecular weight: 366.26) Y2-1: 4,4'-diaminodiphenyl ether (molecular weight: 200.24) Y2-2: Shin-Etsu Chemical Co., Ltd. KF-8010 (diamine with a siloxane skeleton, molecular weight: 860) Y2-3: Priamine 1075 (dimer diamine, molecular weight: 539.52) manufactured by Croda Japan
[0080] <Production of anionic electrodeposition coating composition> [Example 1] In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, 45.0 parts of polyimide resin (A1), 27.5 parts of ethylene glycol monohexyl ether, 15.0 parts of diethylene glycol dimethyl ether, and 2.5 parts of cyclohexanone were charged, and the mixture was heated to 120°C under a nitrogen gas atmosphere and stirred to completely dissolve the polyimide resin. After that, the mixture was cooled to 70°C, and 2.0 parts of dimethylaminoethanol were added while maintaining the temperature at 70°C, and the mixture was stirred for 10 minutes. Next, 6.9 parts of Desmodur BL3272 MPA (manufactured by COVESTRO AG, non-volatile content concentration 72%) (containing 5.0 parts of blocked polyisocyanate compound (D1) and 1.9 parts of propylene glycol methyl ether acetate) as a curing agent and 0.5 parts of Surfynol 420 (manufactured by Shin-Etsu Chemical Co., Ltd., non-ionic surfactant) as an additive were added so that the solid content was 5 parts, and the mixture was further stirred for 10 minutes. Thereafter, 400.6 parts of ion-exchanged water was gradually added dropwise and mixed over 30 minutes to obtain an anionic electrodeposition coating composition with a non-volatile content of 10% and an electrical conductivity of 770 μS / cm.
[0081] [Examples 2 to 17], [Comparative Examples 1 to 3] The anionic electrodeposition coating compositions of Examples 2 to 17 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the raw materials and blending amounts of Example 1 were changed to those shown in Tables 2 and 3.
[0082] [Table 2]
[0083] [Table 3]
[0084] In Tables 2 and 3, the symbols are as follows: D1: Desmodur BL3272 MPA (COVESTRO AG, non-volatile content 72%), blocked polyisocyanate compound D2: TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, multifunctional epoxy resin, non-volatile content 100%)
[0085] <Storage stability> The resulting anionic electrodeposition coating composition was allowed to stand in a thermostatic chamber at 25° C. for one month, after which the appearance properties were evaluated. A: No change in appearance. Good. B: There is some change in the hue and turbidity of the paint, but there is no separation or sedimentation, and the appearance is uniform. There are no problems in practical use. C: Abnormalities such as gelation, separation, and sedimentation occurred. Not suitable for practical use.
[0086] [Preparation of anionic electrocoated panels] The obtained anionic electrodeposition coating composition was placed in a tank, a SUS304 steel plate was used as the cathode, and a copper material (10 cm x 10 cm x 0.30 mm thick) was immersed as the coating material, and anionic electrodeposition coating was performed by adjusting the voltage and coating time at a liquid temperature of 25°C so that the thickness of the dried coating film was 20 μm (electrodeposition coating plate 1) and 40 μm (electrodeposition coating plate 2: thick film coating), and the excess paint was washed off with water in a water bath. After that, it was dried at a temperature of 100°C for 30 minutes and then baked at a temperature of 200°C for 30 minutes to prepare an electrodeposition coating plate for evaluation.
[0087] <Paint appearance 1> The surface of the electrodeposition coated plate 1 obtained above was visually evaluated according to the following criteria. A: A smooth and uniform coating film is obtained. Good. B: The coating film is uneven, but does not pose a problem for practical use. C: The coating has pinholes, popping, and loss of smoothness. Not suitable for practical use.
[0088] <Paint appearance 2> The surface of the electrodeposition coated plate 2 (thick film coating) obtained above was visually evaluated according to the following criteria. A: A smooth and uniform coating film is obtained. Good. B: The coating film is uneven, but does not pose a problem for practical use. C: The coating has pinholes, popping, and loss of smoothness. Not suitable for practical use.
[0089] <Adhesion to substrate (cross-cut peel test)> For the obtained electrocoated plate 2, 11 perpendicular scratches were made in a checkerboard pattern at 1 mm intervals with a cutter knife so that they reached the substrate. Cellophane tape was then adhered to the scratched coating surface, and the cellophane tape was then quickly peeled off by hand and the peeling condition of the scratched coating area was observed. A: No peeling at all. Good. B: Peeling occurred over an area of more than 0% but less than 5% of the scratched coating area (based on 100%). No practical problems. C: Peeling occurred over an area of more than 5% of the scratched coating area (100%). Not suitable for practical use.
[0090] <Insulation properties (dielectric breakdown voltage measurement)> The dielectric breakdown strength was measured using the electrodeposition coated plate 2 according to a method in accordance with JIS C 2110-1:2016. That is, using an ultra-high voltage withstand voltage tester 7473 (manufactured by Keisoku Gijutsu Kenkyusho Co., Ltd.), the electrodeposition test plate 2 was immersed in insulating oil and fixed to the electrode, and a voltage was continuously applied while increasing the voltage at a voltage increase rate of 100 V / sec. The voltage at which a current of 2 mA was detected was taken as the dielectric breakdown voltage to evaluate the insulation properties of the coating film. A: Dielectric breakdown voltage is 3.0 kV or more. Good. B: Dielectric breakdown voltage is 2.0 kV or more and less than 3.0 kV. No problem in practical use. C: Dielectric breakdown voltage is less than 2.0 kV. Not suitable for practical use.
[0091] <Heat resistance> The electrocoated plate 2 was held at 200°C for 500 hours in an incubator with safety door SPHH-202 manufactured by Espec Co., Ltd., and the insulation of the plate after the test was evaluated. The insulation was evaluated in the same manner as in the dielectric breakdown voltage measurement. A: Dielectric breakdown voltage is 3.0 kV or more. Good. B: Dielectric breakdown voltage is 2.0 kV or more and less than 3.0 kV. No problem in practical use. C: Dielectric breakdown voltage is less than 2.0 kV. Not suitable for practical use.
[0092] <Thermal shock resistance 1> Using a thermal shock tester TSE-12-A manufactured by Espec, the electrocoated plate was cooled and held at -40°C for 15 minutes, then immediately heated to 180°C and held there for 15 minutes, and 500 consecutive cycles of thermal shock tests were performed, and the insulation properties of the plate after the tests were evaluated. The insulation properties were evaluated in the same manner as in the dielectric breakdown voltage measurement. A: Dielectric breakdown voltage is 3.0 kV or more. Good. B: Dielectric breakdown voltage is 2.0 kV or more and less than 3.0 kV. No problem in practical use. C: Dielectric breakdown voltage is less than 2.0 kV. Not suitable for practical use.
[0093] <Thermal shock resistance 2> Using a thermal shock tester TSE-12-A manufactured by Espec Corp., the electrodeposition coated plate was cooled and held at -40°C for 15 minutes, then immediately heated to 180°C and held there for 15 minutes, and 500 consecutive cycles of thermal shock tests were performed, with each cycle counting as one cycle, and the adhesion of the coated plate to the substrate was evaluated after the test. The method of evaluation of the adhesion to the substrate was the same as that of the cross-cut peel test described above. A: No peeling at all. Good. B: Peeling occurred over an area of more than 0% but less than 5% of the scratched coating area (based on 100%). No practical problems. C: Peeling occurred over an area of more than 5% of the scratched coating area (100%). Not suitable for practical use.
[0094] Tables 2 and 3 show the compositions of the anionic electrodeposition paints obtained in Examples 1 to 17 and Comparative Examples 1 to 3, and the evaluation results of the physical properties of the coating films obtained from these anionic electrodeposition paints.
[0095] As shown in Tables 2 and 3, the anionic electrocoating paints of Examples 1 to 17 had good physical properties in all respects, whereas the anionic electrocoating paints of Comparative Examples 1 to 3 had poor physical properties in some respects, and no paints were found to have all good properties.
Claims
1. An anionic electrodeposition coating composition comprising a polyimide resin (A) which is a polycondensation product of an acid dianhydride and a diamine, and a basic compound (B), At least one of the acid dianhydride and the diamine constituting the polyimide resin (A) has a bisphenol skeleton, An anionic electrodeposition coating composition having an electrical conductivity of 300 to 2,500 μS / cm.
2. 2. The anionic electrodeposition coating composition according to claim 1, wherein the total content of the acid dianhydride and the diamine having a bisphenol skeleton is 40 mol % or more, based on 100 mol % of the total of the acid dianhydride and the diamine.
3. 2. The anionic electrodeposition coating composition according to claim 1, wherein the polyimide resin (A) has a hydroxyl group in the molecule.
4. 2. The anionic electrodeposition coating composition according to claim 1, further comprising a curing agent (D).
5. 2. The anionic electrodeposition coating composition according to claim 1, wherein the basic compound (B) contains at least one of an alkanolamine compound and a heterocyclic amine compound.
6. The anionic electrodeposition coating composition according to claim 1, further comprising an organic solvent (C), the organic solvent (C) comprising an organic solvent (C-1) having an ether group in the molecule.
7. A coated article obtained by electrodeposition coating of an anionic electrodeposition coating composition according to any one of claims 1 to 6 on a substrate.
Citation Information
Patent Citations
Electrodeposition coating composition
JP1997124978A
Resin composition and aqueous electrodeposition coating
JP2006052268A
Polyimide electrodeposition coating material and method for producing the same
JP2011256318A
Resin for insulation film formation, varnish, electrodeposition liquid, and method for manufacturing insulation conductor
JP2019094404A
Electro-deposition coating composition and manufacturing method of article
JP2023080873A